Ultrasound Detection of Extracranial Carotid Artery Aneurysms: A Case Report - Fabrizio D’Abate (Radcliffe Medical Media, 2020)
The ultrasound definition of extracranial carotid artery aneurysms (ECCAs) is unclear. The threshold diameter to use for defining an extracranial carotid artery as aneurysmal is still debated. Similarly, the ultrasound method of choice for measuring the maximum diameter of ECCAs has not been agreed. In this paper we report the case of a patient with a fusiform aneurysm at the level of the carotid artery bifurcation and a large saccular aneurysm of the proximal internal carotid artery, and discuss the information essential to acquire when ECCAs are detected with ultrasound.